1997
DOI: 10.1182/blood.v90.8.2911
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Secretion Is Impaired by Inhibitors of the Atp Binding Cassette Transporter, ABC1

Abstract: The production of interleukin-1β (IL-1β), a powerful mediator of inflammation, is tightly regulated at several levels. However, in some pathologic conditions, a pharmacologic treatment is required to control the toxicity of excessive extracellular IL-1β. Because of the heavy side effects of most therapies used in IL-1β–mediated pathologies, a goal of pharmacologic research is the development of selective anti–IL-1β drugs. We show here that the sulfonylurea glyburide, currently used in the oral therapy of nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(100 citation statements)
references
References 21 publications
6
92
1
1
Order By: Relevance
“…These observations are consistent with the fact that IL-1b secretion is sensitive to methylamine [6], a drug that disturbs endocytosis [26]. Based on pharmacological studies employing the sulfonylurea glyburide (10 lM) along with expression-inhibition studies employing antisense techniques, an ABC transporter, ABC1, has been implicated in the overall process of IL-1b secretion [27,28] and therefore might mediate IL-1b translocation from the cytoplasm to the lumen of the endolysosomal compartment. Interestingly, glyburide also appears to inhibit nonclassical secretion of macrophage migration inhibitory factor (J. Bernhagen, RWTH Aachen, Germany, personal communication), an inflammatory cytokine mediating a number of immune and inflammatory diseases, e.g.…”
Section: Cytokines: Interleukin-1b Thioredoxin and Macrophage Migratsupporting
confidence: 72%
“…These observations are consistent with the fact that IL-1b secretion is sensitive to methylamine [6], a drug that disturbs endocytosis [26]. Based on pharmacological studies employing the sulfonylurea glyburide (10 lM) along with expression-inhibition studies employing antisense techniques, an ABC transporter, ABC1, has been implicated in the overall process of IL-1b secretion [27,28] and therefore might mediate IL-1b translocation from the cytoplasm to the lumen of the endolysosomal compartment. Interestingly, glyburide also appears to inhibit nonclassical secretion of macrophage migration inhibitory factor (J. Bernhagen, RWTH Aachen, Germany, personal communication), an inflammatory cytokine mediating a number of immune and inflammatory diseases, e.g.…”
Section: Cytokines: Interleukin-1b Thioredoxin and Macrophage Migratsupporting
confidence: 72%
“…Recently it has been found that glyburide also affects innate immunity by inhibiting the inflammasome in various settings [34][35][36][37]. Typically, this is taken as evidence, that a key step in inflammasome activation is a potassium efflux [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of their release is still unclear, although FGF-1 can be released in response to heat shock (Jackson et al 1992), and FGF-2 may be released through exocytosis, as shown by the fact that depleting cells of ATP inhibits the release of this factor (Miyakawa and Imamura 2003). In contrast, although they lack conventional secretion signal sequences, FGF-9, -16, and -20 contain a bipartite, non-cleavable signal peptide sequence for entry into the conventional secretory pathway (Hamon et al 1997).…”
Section: Discussionmentioning
confidence: 99%